The Common Reintegration of Death in Heidegger and Juan Ramón Jiménez - Olivé, Laia (2025)
The aim of this article is to link the Heideggerian investigation of death —in its natural sense as a future fact and in its existential sense as an imminent possibility of existence— with Juan Ramón Jiménez’s poetic treatment of death, in whose poems both senses are present. Although the connection between the philosopher and the poet had already been noted by some researchers —though only in a limited way—, the novelty of the present article lies in showing in detail that, in the work of both authors, a reintegration of death into human existence takes place, through Heidegger's philosophical grounding and through the content that appears in certain poems by Juan Ramón Jiménez.